1998
DOI: 10.1111/j.1348-0421.1998.tb02261.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of the actA Gene of Listeria monocytogenes Isolated from Human

Abstract: The region encoding proline-rich units of actA genes was amplified from 24 strains of Listeria monocytogenes using polymerase chain reaction (PCR). PCR products of 13 strains showed the expected size of 623 bp, whereas those of 11 strains showed a short size of 518 bp. The shortening of these PCR products resulted from the deletion of one proline-rich unit. These results indicate that ActA proteins are divided into at least two different types which are unrelated to bacterial serotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…In addition, ActA was detected in most strains of L. monocytogenes tested; the only exceptions were one serovar 3a strain and one serovar 4ab strain. Moriishi et al (30) sequenced the actA gene of 24 strains isolated from healthy humans and patients and found two groups, one of which was characterized by deletion of one proline-rich repeat. No correlation between this classification and serovars was found.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ActA was detected in most strains of L. monocytogenes tested; the only exceptions were one serovar 3a strain and one serovar 4ab strain. Moriishi et al (30) sequenced the actA gene of 24 strains isolated from healthy humans and patients and found two groups, one of which was characterized by deletion of one proline-rich repeat. No correlation between this classification and serovars was found.…”
Section: Discussionmentioning
confidence: 99%
“…PCR-based methods for discrimination of B. pseudomallei and B. mallei from ara ϩ biotypes such as B. thailandensis have been developed based on the uneven conservation of type III secretion system genes (19,28) and show promise in a clinical setting (16 25). Natural diversity exists in the prevalence and sequences of bacterial factors required for actin-dependent movement, including Listeria ActA (10,17), Shigella and enteroinvasive Escherichia coli IcsA (4), Rickettsia sp. RickA (9,14), and the Tir and TccP proteins of attaching and effacing E. coli (7,20,22).…”
mentioning
confidence: 99%
“…They also reported that the actA gene Type II sequence was detected in the ribotype dd0647 of L. monocytogenes implicated in at least four human foodborne listeriosis outbreaks. Their report suggests that further epidemiological and pathogenic investigation of L. monocytogenes of actA gene Type II may demonstrate the significance of the actA gene in the development of listeriosis (12,28).…”
Section: Discussionmentioning
confidence: 99%
“…The patterns of the amplified products were recorded and analyzed using a Fluor-S TM Multi-Imager (Bio-Rad, U.S.A.). The type of each actA gene product was determined by the size of the PCR product reflecting the nucleotide sequence of the actA gene (Type I with two LUs corresponds to a 623 bp product and Type II, lacking one LU, corresponds to a 518 bp product) (12). RAPD profiles were obtained following the general protocol described in the WHO Multicenter Study on L. monocytogenes subtyping (27).…”
Section: Pcr Amplification Of Randomly Amplified Polymorphic Dna (Rapd)mentioning
confidence: 99%